PENGARUH PERBEDAAN SUHU DAN LAMA PENYIMPANAN ASI PERAH TERHADAP KANDUNGAN ZAT MAKRONUTRIEN - Febriniwati Rifdi; Billy Harnaldo Putra; Sonia Maharani (Universitas Fort de Kock Bukittinggi, 2022)
Expressed breast milk is breast milk that is taken by expressing it from the breast to be stored and later given to the baby. A working mother, who still wants to give exclusive breastfeeding, will find it difficult to give her breast milk directly so that breast milk is given in the form of expressed milk. Basically, breast milk is sterile, but during storage at room temperature, the number of bacteria can increase and decrease the nutrients contained in breast milk. The nutritional components contained in breast milk are macronutrients such as protein, carbohydrates and fats. This study was a pure experimental study using post tes only group design. The purpose of this study was to examine the effect of differences in temperature and storage duration of Dairy Milk on the content of macronutrients (protein, carbohydrates, fat). The sample in this study were exclusively breastfeeding mothers for 3 to 6 months who were in the working area of the Nilam Sari Public Health Center, Bukittinggi City. Statistical test using One Way Annova test. The results of this study indicate that the levels of protein, carbohydrates, and fat in breast milk stored for 6 hours at room temperature 20-250C, for 7 days and 14 days in a freezer at a temperature of -150C experienced a significant decrease with a p value of 0.000 < 0.05. The conclusion of this study is that there is an effect of temperature and storage time of expressed breast milk on the content of macronutrients (protein, carbohydrates, fat). Therefore, breast milk should be given directly to the baby. However, for working mothers, the storage of expressed breast milk can still be done by taking into account the sterility of the breast milk container, the storage temperature and not repeating the storage. Keywords : Storage Temperature, Storage Duration, Macronutrient Of Breast Milk